Book Review: The Doctrine of Ahl as-Sunnah Versus the “Salafi” Movement - Sabah Hussain (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
This brief but excellent book by the Iraqi scholar al-Zahawi (1863-1936) is published in English for the first time, by Allah’s grace, to give our Muslim brother in the West the necessary historical background on important questions of belief and methodology which are currently under attack from certain quarters of our Community. It is a companion volume to our two books entitled Islamic Doctrine and Beliefs According to Ahl al-Sunna.  In essence, Salafism and Wahhabism are the same, but the latter is identified by its founder while the former takes the name of the Salaf and makes it its own. Yet both Salafism and Wahhabism depart from the belief and practice of the Salaf, as the present book abundantly makes clear.